A Case Study of Unusual Etiology of Anterior Uveitis with Ocular Hypertension-Iris Metastasis of Primary Lung Adenocarcinoma - Lin, Alexander D (University Clinical, Education & Research Associate (UCERA), 2014)
This is a case of anterior uveitis in a 50 year-old man caused by lung adenocarcinoma metastasis to the iris. The patient was initially worked up for pneumonia and was discovered to have multiple lung lesions on computed tomography scan. Prior to discharge, the patient began complaining of ocular redness, pain, photophobia and decreased visual acuity. The patient was given an initial diagnosis of anterior uveitis with uveitic glaucoma, which was later confirmed to be secondary to lung adenocarcinoma metastasis to the iris. Metastasis to the iris is a particularly rare cause of anterior uveitis and may inadvertently be left out of a physician's differential diagnosis. This case illustrates a rare, but clinically important cause of anterior uveitis with intraocular hypertension, which should be considered in all cases of ocular redness and pain.